2023
DOI: 10.3389/fendo.2023.1107182
|View full text |Cite
|
Sign up to set email alerts
|

Regulators involved in trophoblast syncytialization in the placenta of intrauterine growth restriction

Abstract: Placental dysfunction refers to the insufficiency of placental perfusion and chronic hypoxia during early pregnancy, which impairs placental function and causes inadequate supply of oxygen and nutrients to the fetus, affecting fetal development and health. Fetal intrauterine growth restriction, one of the most common outcomes of pregnancy-induced hypertensions, can be caused by placental dysfunction, resulting from deficient trophoblast syncytialization, inadequate trophoblast invasion and impaired vascular re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 225 publications
(276 reference statements)
0
3
0
Order By: Relevance
“…Indeed, as described during the in vitro VST differentiation of human chorionic villi trophoblasts and BeWo cells, E-cadherin levels are significantly increased during earlier stages of syncytialization but rapidly decreased as syncytialization progresses in the spontaneous and induced syncytialization systems [72]. Although the literature regarding the relationship between E-cadherin expression and gestational pathologies is controversial, it is predominantly in the direction of an increased expression of E-cadherin in PE and FGR [73,74]. In this context, we found that IFNγ and GM-CSF also had opposing effects on morphologic trophoblast differentiation, with IFNγ increasing E-cadherin expression, whereas GM-CSF reduced it in VST/BW cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, as described during the in vitro VST differentiation of human chorionic villi trophoblasts and BeWo cells, E-cadherin levels are significantly increased during earlier stages of syncytialization but rapidly decreased as syncytialization progresses in the spontaneous and induced syncytialization systems [72]. Although the literature regarding the relationship between E-cadherin expression and gestational pathologies is controversial, it is predominantly in the direction of an increased expression of E-cadherin in PE and FGR [73,74]. In this context, we found that IFNγ and GM-CSF also had opposing effects on morphologic trophoblast differentiation, with IFNγ increasing E-cadherin expression, whereas GM-CSF reduced it in VST/BW cells.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced blood flow to the fetus will cause a lower or intermittent provision of nutrients and oxygen, and there could be episodes of oxidative stress that can lead to a misfolded protein accumulation (51,52). Hypoxic conditions have also been linked to a reduced activity of differentiation pathways of trophoblasts, such as syncytialization (53,54). Thus, a maternal-fetal interface imbalance mediated by impaired trophoblast function may compromise the normal development of the large human fetal brain, taking into account its high demand of oxygen and nutrients (15,55).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that hypoxia plays a different role in placentogenesis depending on gestational age: in the first trimester of pregnancy, it promotes trophoblast invasion and angiogenesis [58], but a prolonged hypoxic condition beyond the first trimester causes deficient trophoblast syncytialization, inadequate trophoblast invasion, and impaired vascular remodeling, resulting in placental dysfunction and pregnancy-induced hypertension such as pre-eclampsia/intrauterine growth restriction [59,60]. Some miRNAs are hypoxia-responsive molecules [61][62][63], and among which are placenta-specific miR-NAs, identified in the present study as being pre-eclampsia-associated markers.…”
Section: Discussionmentioning
confidence: 99%